2012
DOI: 10.1128/aem.02063-12
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Enumeration of Viable Lactobacillus plantarum WCFS1 Cells after Single-Droplet Drying

Abstract: dSurvival of probiotic bacteria during drying is not trivial. Survival percentages are very specific for each probiotic strain and can be improved by careful selection of drying conditions and proper drying carrier formulation. An experimental approach is presented, comprising a single-droplet drying method and a subsequent novel screening methodology, to assess the microbial viability within single particles. The drying method involves the drying of a single droplet deposited on a flat, hydrophobic surface un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…The minimum detection limit for this QFM was ∼ 10 7 cells mL -1 for B. longum ATCC 15707 and an ideal cell density between 1 ∼ 3 x 10 8 cells mL -1 gave 50 to 200 cells per image, which is in accordance with the recommended cell density of 10 8 cells mL -1 for Bifidobacterium UCC 35612 (1). A similar study was conducted by measuring viability of L. plantarum WCFS1 in 20 images with 200 to 500 cells per image (2,080 by 1,544 pixels) (19). Another study suggested cell density of 40 – 50 cells per image but the size of the images was not mentioned so comparison of the cell density between different studies is difficult (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum detection limit for this QFM was ∼ 10 7 cells mL -1 for B. longum ATCC 15707 and an ideal cell density between 1 ∼ 3 x 10 8 cells mL -1 gave 50 to 200 cells per image, which is in accordance with the recommended cell density of 10 8 cells mL -1 for Bifidobacterium UCC 35612 (1). A similar study was conducted by measuring viability of L. plantarum WCFS1 in 20 images with 200 to 500 cells per image (2,080 by 1,544 pixels) (19). Another study suggested cell density of 40 – 50 cells per image but the size of the images was not mentioned so comparison of the cell density between different studies is difficult (12).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative fixation method has been reported by other, bioadhesive slides (Excell AdhesionTM, Fisher Scientific) which showed good cell trapping, but compounds present on the slides caused mortality or affected permeability of the cell membrane, thus inducing mortality of some pure cultures and river water microbes (5). Recently, a low-melting point agarose gel supplemented with Bac Light stains was used to rehydrate and determine viability of dried cell particles deposited on Anopore chips (19). However, Anopore chips are expensive for routine determination of live or dead cells in a product.…”
Section: Discussionmentioning
confidence: 99%
“…Цей штам є пробіотичним, він детально вивчений і описаний за послідовністю цілого геному. Штам є представником мікробіоценозу людини, підтверджено його вплив на формування імуностатусу організму (Perdana et al, 2012;Bron et al, 2006).…”
Section: вступunclassified
“…Approximately 20 images were captured per sample at a magnification of 630x using an Olympus XC30 camera (Olympus, Japan) and CellSens imaging software (Olympus, Japan). Image analysis was performed using a Matlab script to discriminate between red and green cells, as was described earlier by Perdana et al (2012).…”
Section: Addition Of Stains Before and After Pef Treatmentmentioning
confidence: 99%
“…Carrier materials with a high glass transition temperature (Tg) are expected to provide a glassy matrix earlier during droplet drying or soon after drying upon cooling (Perdana et al, 2014b(Perdana et al, , 2012. We estimated the Tg as function of moisture content for every component studied in this work using the Couchman-Karasz theory (Fig.…”
Section: Effect Of Physicochemical Matrix Propertiesmentioning
confidence: 99%